Method for manufacturing radio wave absorber, radio wave absorber, and radio wave absorbing article

By using magnetic particles with an aspect ratio of 3.0 or less when manufacturing an electric wave absorber in a 3D printer, the problem of large polarization dependence of the electric wave absorber is solved, and the radar recognition accuracy and system reliability are improved.

CN119586338APending Publication Date: 2025-03-07FUJIFILM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380054886.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-20
Filing Date
2023-07-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, when using a 3D printer to manufacture an electric wave absorber, the transmission attenuation characteristics are easily affected by the incident angle of the electric wave, resulting in a large polarization dependence and affecting the radar recognition accuracy.

Method used

By using magnetic particles having an aspect ratio of 3.0 or less, such as hexagonal ferrite, combined with an adhesive, three-dimensional modeling is performed through a 3D printer to produce an electric wave absorber with a low polarization dependence.

Benefits of technology

It reduces the polarization dependence of the radio wave absorber, improves the radar recognition accuracy and system reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119586338A_ABST
    Figure CN119586338A_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a radio wave absorber, a radio wave absorber comprising magnetic particles and a binder, and a radio wave absorbing article comprising the radio wave absorber, the method for manufacturing the radio wave absorber comprises a step of three-dimensionally shaping a composition containing one or more particles selected from the group consisting of magnetic particles and dielectric particles and a binder by a three-dimensional printer, wherein the aspect ratio of the particles is 3.0 or less. Among squareness ratios measured in each of seven predetermined directions of the radio wave absorber, the maximum value is SQmax, the minimum value is SQmin, and the ratio of SQmax to SQmin (SQmax / SQmin) is less than 1.35.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a radio wave absorber, a radio wave absorber and a radio wave absorbing article. Background Art

[0002] Patent Document 1 discloses a method for producing a radio wave absorber (referred to as “electromagnetic wave absorber” in Patent Document 1).

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-133416 Summary of the invention

[0006] Technical issues to be solved by the invention

[0007] In detail, Patent Document 1 discloses the use of a 3D (three dimensions) printer to stack and mold radio wave absorbers. According to the three-dimensional molding using a 3D printer, it is possible to directly mold various shapes of molded products from shape data. Therefore, in recent years, for example, three-dimensional molding using a 3D printer has attracted attention as a molding method for small batch products, prototypes produced on order, etc.

[0008] Under such circumstances, an object of one embodiment of the present invention is to provide a new method for manufacturing a radio wave absorber by three-dimensional modeling using a 3D printer.

[0009] Means for solving technical problems

[0010] In recent years, radars that are used to identify objects by transmitting and receiving radio waves have attracted much attention as electronic devices that use radio waves. For example, vehicle-mounted radars can identify the existence of objects, the distance to objects, etc. by transmitting radio waves and receiving radio waves reflected by objects (pedestrians, vehicles, etc.). In order to prevent collisions with objects, the car's automatic driving control system can automatically brake to stop the car or automatically control the speed to maintain a distance from the object based on the results of radar identification of the object.

[0011] As described above, in order to improve the reliability of the system that performs various controls based on the results of radar recognition, it is expected to improve the performance of the radar. Therefore, in recent years, research has begun to be conducted on providing a radio wave absorber on the front side (the incident side of the radio wave incident from the outside) of the radar's radio wave transceiver unit to improve the recognition accuracy.

[0012] It is preferred that the radio wave absorber has excellent transmission attenuation characteristics. For example, from the viewpoint of improving the recognition accuracy of the radar, a radio wave absorber with excellent transmission attenuation characteristics is preferred. Moreover, in various other uses of the radio wave absorber, a radio wave absorber with excellent transmission attenuation characteristics is also desired. Therefore, the inventors have repeatedly studied the transmission attenuation characteristics of the radio wave absorber three-dimensionally molded using a 3D printer. As a result, in the radio wave absorber three-dimensionally molded using a 3D printer, it is newly clarified that the transmission attenuation characteristics are prone to change according to the incident angle of the radio wave (hereinafter referred to as "polarization dependence"). However, when used in various applications, the radio wave can be incident on the radio wave absorber from various angles. Therefore, it is preferred to reduce the above-mentioned polarization dependence. Therefore, the inventors have further repeatedly conducted in-depth research and newly discovered that when the radio wave absorber is molded by three-dimensional molding using a 3D printer, a radio wave absorber with less polarization dependence can be manufactured by using particles with an aspect ratio of less than 3.0.

[0013] That is, one embodiment of the present invention is as follows.

[0014] [1] A method for producing a radio wave absorber, comprising the steps of three-dimensionally shaping a composition comprising one or more particles selected from the group consisting of magnetic particles and dielectric particles and a binder using a three-dimensional printer (hereinafter also referred to as a "3D printer");

[0015] The aspect ratio of the particles is 3.0 or less.

[0016] [2] The method for producing a radio wave absorber according to [1], wherein:

[0017] The above particles are magnetic particles.

[0018] The magnetic particles are particles of hexagonal ferrite.

[0019] [3] The method for producing a radio wave absorber according to [2], wherein:

[0020] The above-mentioned hexagonal ferrite is a substituted hexagonal ferrite.

[0021] [4] The method for producing a radio wave absorber according to [3], wherein:

[0022] The substituted hexagonal ferrite is a magnetoplumbite hexagonal ferrite having a composition represented by Formula 1 below.

[0023] [Chemical formula 1]

[0024] Formula 1

[0025] AFe (12-x) AI x O19

[0026] In Formula 1, A represents one or more atoms selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 0.50≤x≤8.00.

[0027] [5] The method for producing a radio wave absorber according to [4], wherein:

[0028] In Formula 1, the atom represented by A includes Sr.

[0029] [6] The method for producing a radio wave absorber according to [1], wherein:

[0030] The above particles are dielectric particles,

[0031] The dielectric particles are carbon particles.

[0032] [7] A radio wave absorber comprising magnetic particles and a binder, wherein:

[0033] An arbitrary axial direction in a plane perpendicular to the thickness direction of the radio wave absorber is defined as a 0° direction.

[0034] Based on the above axial direction, the direction of 30° rotation, 60° rotation, 90° rotation, 120° rotation, and 150° rotation in the clockwise direction are respectively designated as the 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction.

[0035] The maximum value of the squareness ratios measured in the thickness direction, 0° direction, 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction of the radio wave absorber is defined as SQ max , set the minimum value to SQ min , SQ max With SQ min The ratio (SQ max / SQ min ) is less than 1.35.

[0036] [8] The radio wave absorber according to [7], wherein

[0037] The aspect ratio of the magnetic particles is 3.0 or less.

[0038] [9] The radio wave absorber according to [7] or [8], wherein

[0039] The magnetic particles are particles of hexagonal ferrite.

[0040]

[10] The radio wave absorber according to [9], wherein

[0041] The above-mentioned hexagonal ferrite is a substituted hexagonal ferrite.

[0042]

[11] The radio wave absorber according to

[10] , wherein

[0043] The substituted hexagonal ferrite is a magnetoplumbite hexagonal ferrite having a composition represented by Formula 1 below.

[0044] [Chemical formula 2]

[0045] Formula 1

[0046] AFe (12-x) AI x O 19

[0047] In Formula 1, A represents one or more atoms selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 0.50≤x≤8.00.

[0048]

[12] The radio wave absorber according to

[11] , wherein

[0049] In Formula 1, the atom represented by A includes Sr.

[0050]

[13] A radio wave absorbing article comprising the radio wave absorber according to any one of [7] to

[12] .

[0051] Effects of the Invention

[0052] According to one aspect of the present invention, it is possible to provide a new method for manufacturing a radio wave absorber by three-dimensional modeling using a 3D printer. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is an illustration of three-dimensional modeling using a 3D printer with a hot melt lamination method.

[0054] Figure 2 This is a diagram for explaining an example of the measurement direction of the squareness ratio. DETAILED DESCRIPTION

[0055] [Method for producing radio wave absorber]

[0056] One embodiment of the present invention relates to a method for manufacturing a radio wave absorber (hereinafter, also simply described as a "manufacturing method"), which includes the step of molding a composition including one or more particles selected from the group consisting of magnetic particles and dielectric particles and a binder by three-dimensional molding. In the above-mentioned manufacturing method, the aspect ratio of the above-mentioned particles is 3.0 or less.

[0057] In the present invention and this specification, "radio waves" refer to electromagnetic waves with a frequency of 3 terahertz (THz) or less. A "radio wave absorber" has radio wave absorptivity for radio waves of one or more frequencies.

[0058] <Particles>

[0059] (Aspect Ratio)

[0060] In the present invention and this specification, the aspect ratio of a particle selected from the group consisting of magnetic particles and dielectric particles is a value obtained by the following method.

[0061] Powder of particles is extracted from a composition containing particles selected from the group including magnetic particles and dielectric particles, or from a radio wave absorber formed by three-dimensionally modeling the composition by a 3D printer by a known method. A part of the powder of the extracted particles is collected as powder for measurement. Alternatively, a part of the powder is collected from the powder of particles used to prepare the composition as powder for measurement. Here, "powder" means a collection of particles. For example, the powder of particles can be extracted from the radio wave absorber by dissolving the binder contained in the radio wave absorber by a known method, or by heating the radio wave absorber at a high temperature (for example, about 500°C) to volatilize the binder.

[0062] The collected powder for measurement was observed by a scanning electron microscope (SEM: Scanning Electron Microscope) to obtain a SEM image. As a scanning electron microscope, a field emission scanning electron microscope (FE-SEM: Field Emission-Scanning Electron Microscope) was used. In the examples described below, SU8220 manufactured by Hitachi High-Technologies Corporation was used. As observation conditions, the acceleration voltage was set to 5.0 kV, and a secondary electron image was obtained as an SEM image, and the observation magnification was set to 20,000 times.

[0063] In the obtained SEM image, a total of 20 particles showing the overall outline of the particles in the SEM image were randomly selected from the measurement powder, and the position of the major axis of each selected particle was determined. In the SEM image, the straight line with the longest distance between two points on the outline of the particle was set as the "major axis".

[0064] Then, cross-section processing was performed by FIB (Focused Ion Beam) under the conditions of acceleration voltage 30 kV, WD (Working Distance) 8.0 mm, and probe current 1660 pA to expose the cross section of the major axis position determined above for each of the 20 particles selected above.

[0065] The exposed cross section of each particle was observed by SEM to obtain a cross-sectional image. Regarding the SEM observation, the scanning electron microscope and observation conditions used were as described above.

[0066] In the obtained cross-sectional image, the major axis length and the minor axis length are obtained as follows.

[0067] The distance between the two intersections where the major axis intersects the particle's outline is set as the "major axis length". Among the straight lines orthogonal to the major axis, the straight line with the longest distance between the two intersections where the straight line intersects the particle's outline is set as the "minor axis", and the distance between the two intersections where the minor axis intersects the particle's outline is set as the "minor axis length".

[0068] For each particle, the aspect ratio was calculated as “aspect ratio=major axis length / minor axis length” from the major axis length and minor axis length obtained by the above measurement.

[0069] The arithmetic average of the aspect ratios obtained for the 20 particles is taken as the aspect ratio of the particles contained in the composition or the radio wave absorber.

[0070] From the viewpoint of reducing the polarization dependence of the radio wave absorber formed by three-dimensional modeling by a 3D printer, the aspect ratio of the particles contained in the composition used in the three-dimensional modeling in the above-mentioned manufacturing method is 3.0 or less, preferably 2.8 or less, more preferably 2.6 or less, 2.4 or less, 2.2 or less, 2.0 or less, and 1.8 or less. In addition, the above-mentioned aspect ratio can be, for example, 1.0 or more or 1.1 or more.

[0071] The particles are one or more particles selected from the group consisting of magnetic particles and dielectric particles. The composition may also contain different types of particles in any proportion as particles selected from the group consisting of magnetic particles and dielectric particles. This also applies to the radio wave absorber described later. In the present invention and this specification, "magnetism" means ferromagnetism (ferromagnetic property), and "dielectric" means the inherent value of a substance, that is, the volume resistivity (ρ v ) is 1×10 5 Substances with a resistance of Ω·m or above.

[0072] (Dielectric particles)

[0073] As the dielectric particles contained in the above-mentioned composition, as long as the aspect ratio obtained by the method described above is less than 3.0, various dielectric particles can be used. For example, as dielectric particles, carbon particles can be cited. Here, "type" is used in the sense of "including". As carbon particles, particles of various carbon materials such as carbon black and graphite can be cited.

[0074] (Magnetic Particles)

[0075] As the magnetic particles contained in the above-mentioned composition, particles of various magnetic bodies such as ferrite, iron oxide, cobalt, and chromium oxide can be cited. From the viewpoint of radio wave absorbency, the magnetic particles are preferably particles of hexagonal ferrite. The type of magnetic body constituting the magnetic particles can be confirmed by analysis using the X-ray diffraction method. For example, the powder of the magnetic particles can be taken out from the composition containing magnetic particles or the radio wave absorber containing magnetic particles by a known method, and the powder taken out can be analyzed by the X-ray diffraction method. Alternatively, a part of the powder can be collected from the powder of the magnetic particles used to prepare the composition, and the collected powder can be analyzed by the X-ray diffraction method. Alternatively, for example, it can also be confirmed by the following method. A part or all of the radio wave absorber is chopped into small pieces, and after being immersed in a solvent (for example, hexafluoroisopropanol) for 1 to 2 days, it is dried. The dried radio wave absorber is further ground into finer pieces and analyzed by the X-ray diffraction method.

[0076] Hexagonal ferrite particles

[0077] In the present invention and this specification, "particles of hexagonal ferrite" refer to magnetic particles in which the crystal structure of hexagonal ferrite is detected as the main phase by analysis using the X-ray diffraction method. The main phase refers to the structure to which the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by the X-ray diffraction method belongs. For example, when the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by the X-ray diffraction method belongs to the crystal structure of hexagonal ferrite, it is judged that the crystal structure of hexagonal ferrite is detected as the main phase. When only a single structure is detected by the X-ray diffraction method, the detected structure is the main phase. The crystal structure of hexagonal ferrite contains at least iron atoms, divalent metal atoms and oxygen atoms as constituent atoms. In unsubstituted hexagonal ferrite, the atoms constituting the crystal structure of hexagonal ferrite are only iron atoms, divalent metal atoms and oxygen atoms. In contrast, substituted hexagonal ferrite contains iron atoms, divalent metal atoms and oxygen atoms and one or more other atoms as atoms constituting the crystal structure of hexagonal ferrite. The one or more other atoms are usually atoms that replace a portion of iron in the crystal structure of hexagonal ferrite. Divalent metal atoms refer to metal atoms that can become divalent cations as ions, and examples include alkaline earth metal atoms such as strontium atoms, barium atoms, and calcium atoms, and lead atoms. In the present invention and this specification, particles of hexagonal strontium ferrite refer to particles in which the main divalent metal atoms contained in the particles are strontium atoms, and particles of hexagonal barium ferrite refer to particles in which the main divalent metal atoms contained in the particles are barium atoms. The same is true for particles of other types of hexagonal ferrites. The main divalent metal atom refers to the divalent metal atom that accounts for the largest proportion on an atomic % basis among the divalent metal atoms contained in the particle. Among them, rare earth atoms are not included in the above-mentioned divalent metal atoms. The "rare earth atoms" in the present invention and this specification are selected from the group including scandium atoms (Sc), yttrium atoms (Y) and lanthanide atoms. The lanthanide atom is selected from the group consisting of lanthanum atom (La), cerium atom (Ce), praseodymium atom (Pr), neodymium atom (Nd), promethium atom (Pm), samarium atom (Sm), europium atom (Eu), gadolinium atom (Gd), terbium atom (Tb), dysprosium atom (Dy), holmium atom (Ho), erbium atom (Er), thulium atom (Tm), ytterbium atom (Yb) and lutetium atom (Lu).

[0078] As for the particles of hexagonal ferrite, as the hexagonal ferrite constituting the particles, one or more selected from the group consisting of hexagonal strontium ferrite, hexagonal barium ferrite, hexagonal calcium ferrite and hexagonal lead ferrite can be cited. From the viewpoint of radio wave absorptivity in the high frequency band, one or more selected from the group consisting of hexagonal strontium ferrite, hexagonal barium ferrite and hexagonal calcium ferrite is preferred, hexagonal strontium ferrite and / or hexagonal barium ferrite is more preferred, and hexagonal strontium ferrite is further preferred.

[0079] In one embodiment, the hexagonal ferrite particles may be particles of magnetoplumbite-type (commonly referred to as "M-type") hexagonal ferrite. When the magnetoplumbite-type hexagonal ferrite is an unsubstituted type containing no substituted iron atoms, it has a composition formula: AFe 12 O 19 Here, A can represent one or more atoms selected from the group consisting of Sr, Ba, Ca, and Pb, and also includes an embodiment in which two or more of them are contained in any ratio.

[0080] As a preferred hexagonal ferrite from the viewpoint of radio wave absorption, a substituted hexagonal ferrite can be cited. As a specific example of the substituted hexagonal ferrite, a substituted magnetoplumbite hexagonal ferrite in which a part of the iron atoms of the magnetoplumbite hexagonal ferrite is substituted by aluminum atoms can be cited. As one form of such hexagonal ferrite, a hexagonal ferrite having a composition represented by the following formula 1 can be cited.

[0081] [Chemical formula 3]

[0082] Formula 1

[0083] AFe (12-x) AO 19

[0084] In Formula 1, A represents one or more atoms selected from the group consisting of Sr, Ba, Ca and Pb (hereinafter also referred to as "A atoms"). It may be only one kind or may contain two or more kinds in any proportion. From the viewpoint of improving the uniformity of the composition between the particles contained in the radio wave absorber, it is preferably only one kind.

[0085] From the viewpoint of radio wave absorption in the high-frequency band, A in Formula 1 is preferably one or more atoms selected from the group consisting of Sr, Ba and Ca, more preferably one or more atoms selected from the group consisting of Sr and Ba, further preferably including Sr, and further preferably Sr.

[0086] In Formula 1, x satisfies 0.50≤x≤8.00.

[0087] In one embodiment, x can satisfy 1.50≤x≤8.00. From the viewpoint of radio wave absorption in the high frequency band, x is preferably 1.50 or more, more preferably more than 1.50, further preferably more than 2.00, and further preferably more than 2.00. Furthermore, from the viewpoint of magnetic properties, x is 8.00 or less, preferably less than 8.00, more preferably less than 6.00, and further preferably less than 6.00.

[0088] As a specific example of the magnetoplumbite type substituted hexagonal ferrite represented by Formula 1 in which x satisfies 1.50≤x≤8.00, SrFe (9.58) Al (2.42) O 19 、SrFe (9.37) Al (2.63) O 19 、SrFe (9.27) Al (2.73) O 19 、SrFe (9.85) Al (2.15) O 19 、SrFe (10.00) Al (2.00) O 19 、SrFe (9.74) Al (2.26) O 19 、SrFe (10.44) Al (1.56) O 19 、SrFe (9.79) Al (2.21) O 19 、SrFe (9.33) Al (2.67) O 19 、SrFe (7.88) Al (4.12) O 19 、SrFe (7.04) Al (4.96) O 19 、SrFe (7.37) Al (4.63) O 19 、SrFe (6.25) Al (5.75) O 19 、SrFe (7.71) Al (4.29) O 19 , Sr (0.80) Ba (0.10) Ca (0.10) Fe (9.83) Al (2.17) O 19 ,BaFe (9.50) Al (2.50) O 19 , CaFe (10.00) Al (2.00) O 19 and PbFe (9.00) Al (3.00) O 19Etc. And, as a specific example, the substituted hexagonal strontium ferrite described in the embodiment item described later can also be cited. Regarding the composition of the magnetic particles, for example, it can be confirmed by performing high-frequency inductively coupled plasma emission spectroscopy analysis on the solution obtained by dissolving the magnetic particles. As a specific example of the confirmation method, the method described in the embodiment item described later can be cited. Alternatively, after cutting the radio wave absorber to expose the cross section, it is also possible to perform, for example, energy dispersive X-ray analysis on the exposed cross section, thereby confirming the composition of the magnetic particles contained in the radio wave absorber.

[0089] Furthermore, in one embodiment, x can satisfy 0.50≤x<1.50. For example, from the perspective of radio wave absorption in a high frequency band ranging from 35.0 GHz to 66.0 GHz, preferably from 45.0 GHz to 66.0 GHz, and more preferably from 55.0 GHz to 66.0 GHz, x can be 0.50 or more, preferably more than 0.80. Furthermore, from the perspective of magnetic properties, x is preferably less than 1.50, and more preferably less than 1.20.

[0090] In one embodiment, the substituted hexagonal ferrite may have a single crystal phase or may include a plurality of crystal phases. Preferably, the crystal phase is a single phase, and more preferably, it is a magnetoplumbite-type substituted hexagonal ferrite having a single crystal phase.

[0091] The case where "the crystal phase is a single phase" refers to the case where only one diffraction pattern representing an arbitrary crystal structure is observed in the analysis performed by the X-ray diffraction method. For example, the analysis by the X-ray diffraction method can be performed by the method described in the embodiment item described later. In the case where multiple crystal phases are included, in the analysis by the X-ray diffraction method, two or more diffraction patterns representing arbitrary crystal structures are observed. In the attribution of the diffraction pattern, for example, the database of the International Center for Diffraction Data (ICDD: International Centre for Diffraction Data (registered trademark)) can be referenced. For example, for the diffraction pattern of a hexagonal ferrite of the magnetoplumbite type containing Sr, "00-033-1340" of the International Center for Diffraction Data (ICDD) can be referenced. Among them, if a part of the iron atoms are substituted by substitution atoms such as aluminum atoms, the peak position is shifted from the peak position when the substitution atoms are not included.

[0092] Method for producing hexagonal ferrite particles

[0093] There are various methods for producing hexagonal ferrite particles. When the composition used in the above production method contains hexagonal ferrite particles, the production method of hexagonal ferrite particles is not particularly limited. Hereinafter, as an example of a method for producing hexagonal ferrite particles, a solid phase method is described. The solid phase method is a method for producing hexagonal ferrite particles by calcining a mixture obtained by mixing a plurality of solid raw materials.

[0094] As the solid raw materials used in the solid phase method, compounds of iron atoms and compounds of A atoms can be cited. When particles of substituted hexagonal ferrite are manufactured, compounds of substituted atoms can be further cited. These compounds can be oxides, carbonates, etc. About A atoms and substituted atoms as described above. The mixing ratio of multiple solid raw materials can be determined according to the desired hexagonal ferrite composition. A raw material mixture can be obtained by mixing multiple solid raw materials simultaneously or in sequence in any order. In addition, the mixing of solid raw materials is not limited to dry conditions. It can also be carried out under wet conditions, such as adding solvents such as water, and mixing in a slurry state. Regarding the mixing of solid raw materials, it can be carried out by a commercially available mixing device or a mixing device of a known structure. As an example of a mixing device, a paint stirrer can be cited. When mixing, a dispersion medium such as dispersion beads can also be used. Regarding mixing, for example, it can be carried out in an atmospheric atmosphere at room temperature.

[0095] After the above mixing, the obtained raw material mixture can be calcined. During the calcination, the raw material mixture can be crystallized, thereby forming a crystal structure of hexagonal ferrite. As a calcination condition, for example, the calcination temperature can be set in the range of 1000°C to 1500°C. The calcination temperature can be, for example, the atmosphere temperature in the device for calcination (for example, the furnace temperature of a heating furnace). The calcination time can be set in the range of 1 hour to 6 hours. Among them, the above range is for illustration, as long as the calcination is carried out under the conditions that can form the crystal structure of hexagonal ferrite. Calcination can be carried out, for example, in an atmospheric atmosphere.

[0096] Usually, in the calcination of the raw material mixture for the purpose of manufacturing the particles of hexagonal ferrite, a flux (also called a flux) is sometimes added to the powder of the raw material mixture for calcination. As the flux, for example, SrCl2, SrCl2·6H2O, CaCl2·2H2O, MgCl2, KCl, NaCl, BaCl2·2H2O, Na2B4O7, etc. can be cited. According to the research of the present inventors, it was found that if a flux is used, the value of the aspect ratio of the obtained hexagonal ferrite particles tends to increase. Therefore, as an example of a method for controlling the aspect ratio of the hexagonal ferrite particles to be less than 3.0, it is possible to cite a method without using a flux.

[0097] The raw material mixture before the calcination can be put into a dry or wet pulverization process, and / or the calcined product after the calcination can be put into a dry or wet pulverization process. By performing the pulverization process, the size of the particles of the hexagonal ferrite can be adjusted. Regarding pulverization, it can be carried out by a known pulverization mechanism such as a mortar and pestle, a pulverizer (cutter, ball mill, bead mill, roller mill, jet mill, hammer mill, attritor, etc.).

[0098] The calcined product obtained after calcination may be subjected to annealing treatment after being subjected to a step such as pulverization as required. The annealing treatment may be performed in a heating furnace at a furnace temperature of 500 to 1100° C. for about 1 to 10 hours.

[0099] Before and / or after the various steps described above, one or more known steps such as washing and drying may be arbitrarily performed.

[0100] (Volume filling rate)

[0101] In the above-mentioned manufacturing method, the composition for three-dimensional modeling and the radio wave absorber obtained by molding the above-mentioned composition by three-dimensional modeling contain the above-mentioned particles and the binder. In the above-mentioned composition and the above-mentioned radio wave absorber, the filling rate of the above-mentioned particles is not particularly limited. In one embodiment, the above-mentioned filling rate can be less than 35 volume %, for example, it can be in the range of 15 to 35 volume %. In another embodiment, the above-mentioned volume filling rate can also be more than 35 volume %. In this case, the volume filling rate can be, for example, in the range of 35 to 60 volume %, or it can be in the range of 35 to 50 volume %. The volume filling rate represents the volume-based content rate with the total volume of the above-mentioned composition (wherein, when a solvent is included, the solvent is removed. The same applies hereinafter.) or the total volume of the above-mentioned radio wave absorber set to 100 volume %.

[0102] Regarding the composition, the volume filling rate of the above-mentioned particles can be calculated based on the composition of the composition. Regarding the radio wave absorber, for example, the above-mentioned particles can be collected from the radio wave absorber by a known method, and the volume filling rate of the above-mentioned particles can be calculated as "(volume of collected particles / total volume of radio wave absorber)×100". Here, the total volume of the radio wave absorber and the volume of the above-mentioned particles can be calculated by a known method. Alternatively, when the composition of the composition used to make the radio wave absorber is known, the volume filling rate of the above-mentioned particles in the radio wave absorber can also be calculated based on the known composition.

[0103] Furthermore, the volume filling rate of the above-mentioned particles in the radio wave absorber can also be obtained by the following method using a cross-sectional SEM image acquired by a scanning electron microscope (SEM: Scanning Electron Microscope).

[0104] A measurement sample having a square plane with a side of 5 mm is cut from a randomly set position of the radio wave absorber to be measured. A cross-sectional observation sample is prepared from the cut sample. The preparation of the cross-sectional observation sample is carried out by FIB (Focused Ion Beam) processing. The prepared cross-sectional observation sample is observed by SEM, and a cross-sectional image (cross-sectional SEM image) is taken. As the SEM, a field emission scanning electron microscope (FE-SEM) is used. Using FE-SEM, the cross-sectional observation sample is set on the workbench in such a way that the cross section processed by FIB faces upward, and a cross-sectional SEM image with a field of view of 30μm×40μm is obtained under the conditions of an acceleration voltage of 15kV and an observation magnification of 3000 times. The obtained cross-sectional SEM image is binarized, and the proportion (area basis) occupied by the above particles is calculated.

[0105] The above operation can be performed on five measurement samples cut from different positions of the radio wave absorber to be measured to obtain the volume filling rate of the above particles as the arithmetic average of the five values ​​obtained. In addition, if necessary, elemental analysis of the cross-sectional observation sample can be performed, thereby also being able to determine the part of the above particles in the cross-sectional SEM image.

[0106] The volume filling rates of other components described in this specification can also be obtained in the same manner as above.

[0107] <Composition used in three-dimensional modeling>

[0108] In the above production method, the composition for three-dimensional modeling comprises at least the above particles and a binder. The details of the above particles are as described above.

[0109] <<Adhesive>>

[0110] The binder may be, for example, a resin, and examples of the resin include thermoplastic resins and thermosetting resins.

[0111] Examples of the thermoplastic resin include acrylic resin, polyacetal, polyamide, polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene terephthalate-1,4-cyclohexane terephthalate copolymer, polylactic acid, polycarbonate, polystyrene, polyphenylene sulfide, polyvinyl chloride, ABS (acrylonitrile butadiene styrene) resin obtained by copolymerization of acrylonitrile, butadiene and styrene, and AS (acrylonitrile styrene) resin obtained by copolymerization of acrylonitrile and styrene.

[0112] Examples of the thermosetting resin include phenol resin, epoxy resin, melamine resin, urea resin, unsaturated polyester, diallyl phthalate resin, polyurethane resin, and silicone resin.

[0113] Adhesive can also be rubber. As rubber, for example, from the viewpoint of being able to manufacture radio wave absorbers having good miscibility with magnetic particles and excellent durability, weather resistance and impact resistance, butadiene rubber, isoprene rubber, chloroprene rubber, halogenated butyl rubber, fluororubber, polyurethane rubber, acrylic rubber (abbreviated as ACM) obtained by copolymerization of acrylate (e.g., ethyl acrylate, butyl acrylate and 2-ethylhexyl acrylate) and other monomers, ethylene-propylene rubber obtained by coordination polymerization of ethylene and propylene using a Ziegler catalyst, butyl rubber (abbreviated as IIR) obtained by copolymerization of isobutylene and isoprene, styrene-butadiene rubber (abbreviated as SBR) obtained by copolymerization of butadiene and styrene, acrylonitrile-butadiene rubber (abbreviated as NBR) obtained by copolymerization of acrylonitrile and butadiene, silicone rubber, etc. can also be cited.

[0114] When manufacturing a radio wave absorber containing rubber as a binder, the composition may contain various additives other than rubber, such as a vulcanizing agent, a vulcanizing accelerator, a softener, a plasticizer, etc. Examples of the vulcanizing agent include sulfur, organic sulfur compounds, and metal oxides.

[0115] As the binder, for example, thermoplastic elastomer (TPE: Thermoplastic Elastomer) can also be mentioned. As the thermoplastic elastomer, olefin thermoplastic elastomer (TPO: Thermoplastic Olefinic Elastomer), styrene thermoplastic elastomer (TPS: Thermoplastic Styrenic Elastomer), amide thermoplastic elastomer (TPA: Thermoplastic Polyamide Elastomer), polyester thermoplastic elastomer (TPC: Thermoplastic Copolyester) and the like can be mentioned.

[0116] The above-mentioned composition and the radio wave absorber obtained by molding the above-mentioned composition by three-dimensional modeling may contain only one adhesive, or may contain two or more adhesives. The volume filling rate of the adhesive in the above-mentioned composition and the above-mentioned radio wave absorber is not particularly limited, for example, preferably 65 volume % or more, more preferably 65 volume % or more and 92 volume % or less, and further preferably 65 volume % or more and 85 volume % or less. In the case where the above-mentioned composition and the above-mentioned radio wave absorber contain two or more adhesives, the volume filling rate refers to the total volume filling rate of the two or more adhesives. This is also the same for the volume filling rates related to other components.

[0117] <<Additives>>

[0118] The above-mentioned composition and the above-mentioned radio wave absorber can arbitrarily include more than one additive in any proportion, or may not include additives. As other additives, antioxidants, light stabilizers, dispersants, dispersing aids, mildew inhibitors, antistatic agents, plasticizers, impact resistance improvers, crystal nucleating agents, lubricants, surfactants, pigments, dyes, fillers, mold release agents (fatty acids, fatty acid metal salts, oxidized fatty acids, fatty acid esters, aliphatic partial saponification esters, paraffin, low molecular weight polyolefins, fatty acid amides, alkylene bis fatty acid amides, aliphatic ketones, fatty acid lower alcohol esters, fatty acid polyol esters, fatty acid polyethylene glycol esters, modified silicones, etc.), processing aids, antifogging agents, anti-drip agents, antibacterial agents, etc. can be cited. Additives can also be additives in which one component has more than two functions.

[0119] (Antioxidant)

[0120] In one embodiment, an antioxidant can be mentioned as a preferred additive.

[0121] The antioxidant is not particularly limited, and a known antioxidant can be used.

[0122] Examples of antioxidants are described in, for example, "Comprehensive Technology for Polymer Stabilization - Mechanism and Application Development -" edited by Yasukazu Ohkatsu, published by CMC Publishing, which is incorporated herein by reference.

[0123] Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants.

[0124] As the antioxidant, it is preferred to use a phenolic antioxidant and / or an amine antioxidant together with a phosphorus antioxidant and / or a sulfur antioxidant.

[0125] Examples of the phenolic antioxidant include ADEKASTAB AO-20, ADEKASTAB AO-30, ADEKASTAB AO-40, ADEKASTAB AO-50, ADEKASTAB AO-60, ADEKASTAB AO-80, and ADEKASTAB AO-330 from ADEKA CORPORATION, and IRGANOX 1010, IRGANOX 1035, IRGANOX 1076, IRGANOX 1098, IRGANOX 1135, IRGANOX 1330, IRGANOX 1726, IRGANOX 245, IRGANOX 259, IRGANOX 3114, and IRGANOX 565 from BASF Japan Ltd. In addition, both of the above-mentioned "ADEKASTAB" and "IRGANOX" are registered trademarks.

[0126] Examples of the amine antioxidant include SANOL LS-770, SANOL LS-765, and SANOL LS-2626 from Sankyo Lifetech Co., Ltd., ADEKASTAB LA-77, ADEKASTAB LA-57, ADEKASTAB LA-52, ADEKASTAB LA-62, ADEKASTAB LA-63, ADEKASTAB LA-67, ADEKASTAB LA-68, and ADEKASTAB LA-72 from ADEKA CORPORATION, and TINUVIN 123, TINUVIN 144, TINUVIN 622, TINUVIN 765, and TINUVIN 944 from BASF Japan Ltd. In addition, both of the above-mentioned "ADEKASTAB" and "TINUVIN" are registered trademarks.

[0127] Furthermore, as antioxidants, amine compounds that can quench free radicals can also be used. Examples of such amine compounds include polyethylene glycol bis-TEMPO [Sigma-Aldrich Co. LLC.], sebacic acid bis-TEMPO, etc. In addition, "TEMPO" is an abbreviation for tetramethylpiperidin-1-oxyl.

[0128] Examples of the phosphorus antioxidant include ADEKASTAB PEP-8, ADEKASTAB PEP-36, ADEKASTAB HP-10, and ADEKASTAB 2112 from ADEKA CORPORATION and IRGAFOS 168 from BASF Japan Ltd. In addition, both of the above-mentioned "ADEKASTAB" and "IRGAFOS" are registered trademarks.

[0129] Examples of the sulfur-based antioxidant include ADEKASTAB AO-412S and ADEKASTAB AO-503S from ADEKA CORPORATION. In addition, the above-mentioned "ADEKASTAB" is a registered trademark.

[0130] Among the above, the phenolic antioxidant is preferably one or more selected from the group consisting of Adekastab AO-20, Adekastab AO-60, Adekastab AO-80 and IRGANOX 1010; the amine antioxidant is preferably Adekastab LA-52; the phosphorus antioxidant is preferably Adekastab PEP-36; and the sulfur antioxidant is preferably Adekastab AO-412S.

[0131] When the radio wave absorber contains an antioxidant, it may contain only one kind of antioxidant or may contain two or more kinds of antioxidant.

[0132] When the above-mentioned composition and the above-mentioned radio wave absorber contain an antioxidant, the content of the antioxidant in the composition or the radio wave absorber is not particularly limited. For example, from the viewpoint of taking into account both the inhibition of decomposition of the adhesive and the inhibition of the leakage of the antioxidant, it is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the adhesive.

[0133] (Light Stabilizer)

[0134] In one embodiment, a light stabilizer can be mentioned as a preferred additive.

[0135] Examples of the light stabilizer include HALS (that is, hindered amine light stabilizer), ultraviolet absorbers, and singlet oxygen quenchers.

[0136] The HALS may be a high molecular weight HALS, a low molecular weight HALS, or a combination of a high molecular weight HALS and a low molecular weight HALS.

[0137] When the radio wave absorber contains a light stabilizer, it may contain only one type of light stabilizer or may contain two or more types.

[0138] High molecular weight HALS

[0139] In the present invention and this specification, "high molecular weight HALS" means a hindered amine light stabilizer having a weight average molecular weight exceeding 1,000.

[0140] Examples of high molecular weight HALS include oligomer-type HALS, i.e., poly[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino], succinic acid dimethyl-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidinyl condensate, and the like.

[0141] Examples of commercial products of high molecular weight HALS include CHIMASSORB 944LD and TINUVIN 622LD from BASF Japan Ltd. In addition, both of the above-mentioned "CHIMASSORB" and "TINUVIN" are registered trademarks.

[0142] The weight average molecular weight (Mw) in the present invention and this specification is a value measured by gel permeation chromatography (GPC). In the measurement using gel permeation chromatography (GPC), HLC (registered trademark)-8220GPC (manufactured by TOSOH CORPORATION) can be used as a measuring device, and a column can be used in which one of each of TSKgel (registered trademark) Super HZM-M (4.6 mm ID × 15 cm, manufactured by TOSOH CORPORATION), Super HZ4000 (4.6 mm ID × 15 cm, manufactured by TOSOH CORPORATION), Super HZ3000 (4.6 mm ID × 15 cm, manufactured by TOSOH CORPORATION), and Super HZ2000 (4.6 mm ID × 15 cm, manufactured by TOSOH CORPORATION) is connected in series, and THF (tetrahydrofuran) can be used as an eluent.

[0143] As measurement conditions, the sample concentration can be 0.2 mass %, the flow rate can be 0.35 mL / min, the sample injection amount can be 10 μL, and the measurement temperature can be 40° C. As a detector, a differential refractive index (RI) detector can be used.

[0144] The calibration curve can be prepared using “standard samples TSK standard, polystyrene”, “F-40”, “F-20”, “F-4”, “F-1”, “A-5000”, “A-2500”, and “A-1000” manufactured by TOSOH CORPORATION.

[0145] When the composition and the radio wave absorber contain high molecular weight HALS, the content of the high molecular weight HALS in the composition and the radio wave absorber is not particularly limited, and is preferably 0.2% by mass to 10% by mass based on the total mass of the composition or the radio wave absorber.

[0146] From the viewpoint of improving weather resistance, the content of the high molecular weight HALS in the radio wave absorber is preferably set to 0.2 mass % or more relative to the total mass of the radio wave absorber.

[0147] When the content of the high molecular weight HALS in the radio wave absorber is 10 mass % or less relative to the total mass of the radio wave absorber, there is a tendency that a decrease in mechanical strength and the occurrence of blooming can be suppressed.

[0148] Low molecular weight HALS

[0149] In the present invention and this specification, "low molecular weight HALS" means a hindered amine light stabilizer having a molecular weight of 1000 or less (preferably 900 or less, more preferably 600 to 900).

[0150] Examples of low molecular weight HALS include tris(2,2,6,6-tetramethyl-4-piperidinyl)benzene-1,3,5-tricarboxylate, tris(2,2,6,6-tetramethyl-4-piperidinyl)-2-acetoxypropane-1,2,3-tricarboxylate, tris(2,2,6,6-tetramethyl-4-piperidinyl)-2-hydroxypropane-1,2,3-tricarboxylate, tris(2,2,6,6-tetramethyl-4-piperidinyl)triazine-2,4,6-tricarboxylate, and tris(2,2,6,6-tetramethyl-4-piperidinyl)-triazine-2,4,6-tricarboxylate. tetrakis(2,2,6,6-tetramethyl-4-piperidyl)propane-1,1,2,3-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate, 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-n-butylmalonate, and the like.

[0151] Examples of commercially available products of low molecular weight HALS include ADEKASTAB LA-57 and ADEKASTAB LA-52 from ADEKA CORPORATION and TINUVIN 144 from BASF Japan Ltd. In addition, both of the above-mentioned "ADEKASTAB" and "TINUVIN" are registered trademarks.

[0152] When the composition and the radio wave absorber contain low molecular weight HALS, the content of the low molecular weight HALS in the composition and the radio wave absorber is not particularly limited, and is preferably 0.2% to 10% by mass based on the total mass of the composition or the radio wave absorber.

[0153] From the viewpoint of improving weather resistance, the content of the low molecular weight HALS in the radio wave absorber is preferably set to 0.2 mass % or more relative to the total mass of the radio wave absorber.

[0154] When the content of the low molecular weight HALS in the radio wave absorber is 10 mass % or less relative to the total mass of the radio wave absorber, there is a tendency that a decrease in mechanical strength and the occurrence of blooming can be suppressed.

[0155] UV absorber

[0156] Examples of the ultraviolet absorber include 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(3,5-di-tert-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-methyl-phenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-3'-(3 ”,4”,5”,6”-tetrahydrophthalimidemethyl)-5'-methylphenyl]benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-[2-hydroxy-3,5-bis(a,a-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(2-hydroxy-4-octyloxyphenyl)-2H-benzotriazole, 2-(2H- Benzotriazole UV absorbers such as benzotriazole-2-yl)-4-methyl-6-(-(3,4,5,6-tetrahydrophthalimidomethyl)phenol, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2,2',4,4'- Benzophenone-based ultraviolet absorbers such as tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 3,5-di-tert-butyl-4-hydroxybenzoylbenzoic acid n-hexadecyl ester, 1,4-bis(4-benzoyl-3-hydroxyphenoxy)butane, 1,6-bis(4-benzoyl-3-hydroxyphenoxy)hexane, and cyanoacrylate-based ultraviolet absorbers represented by ethyl-2-cyano-3,3-diphenylacrylate.

[0157] Examples of commercially available ultraviolet absorbers include TINUVIN 320, TINUVIN 328, TINUVIN 234, TINUVIN 1577, TINUVIN 622, and IRGANOX series from BASF Japan Ltd., ADEKASTAB LA31 from ADEKA CORPORATION, and SEESORB 102, SEESORB 103, and SEESORB 501 from SHIPRO KASEI KAISHA, LTD. In addition, the above-mentioned "TINUVIN", "IRGANOX", "ADEKASTAB", and "SEESORB" are all registered trademarks.

[0158] When the composition and the radio wave absorber contain an ultraviolet absorber, the content of the ultraviolet absorber in the composition and the radio wave absorber is not particularly limited, and is preferably 0.2% by mass to 10% by mass based on the total mass of the composition or the radio wave absorber.

[0159] From the viewpoint of improving weather resistance, the content of the ultraviolet absorber in the radio wave absorber is preferably set to 0.2% by mass or more relative to the total mass of the radio wave absorber.

[0160] When the content of the ultraviolet absorber in the radio wave absorber is 10% by mass or less relative to the total mass of the radio wave absorber, there is a tendency that a decrease in mechanical strength and the occurrence of blooming can be suppressed.

[0161] -Singlet oxygen quencher-

[0162] When the composition and the radio wave absorber contain a singlet oxygen quencher, the content of the singlet oxygen quencher in the composition and the radio wave absorber is not particularly limited, and is preferably 0.2 mass % to 10 mass % based on the total mass of the composition or the radio wave absorber.

[0163] From the viewpoint of improving weather resistance, the content of the singlet oxygen quencher in the radio wave absorber is preferably set to 0.2 mass % or more relative to the total mass of the radio wave absorber.

[0164] When the content of the singlet oxygen quencher in the radio wave absorber is 10% by mass or less relative to the total mass of the radio wave absorber, a decrease in mechanical strength and the occurrence of blooming tend to be suppressed.

[0165] When the composition and the radio wave absorber contain a light stabilizer, they may contain only one light stabilizer or two or more light stabilizers.

[0166] The composition may or may not contain a solvent. When the composition contains a solvent, the solvent is not particularly limited, and examples thereof include water, an organic solvent, or a mixed solvent of water and an organic solvent.

[0167] As the organic solvent, alcohols such as methanol, ethanol, n-propanol, isopropanol, methoxypropanol, ketones such as acetone, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, acetonitrile, ethyl acetate, toluene, etc. can be cited. Among them, as the solvent, ketones are preferred, and cyclohexanone is more preferred from the viewpoint of drying speed. When the above composition contains a solvent, the content of the solvent in the composition is not particularly limited and can be appropriately determined.

[0168] In the above-mentioned manufacturing method, the above-mentioned composition for three-dimensional modeling can be prepared by mixing the above-mentioned components. The mixing method is not particularly limited, and for example, a method of mixing by stirring can be cited. As a stirring mechanism, a known stirring device can be used. For example, as a stirring device, a mixer such as a paddle mixer and an impeller mixer can be cited. The stirring time can be set according to the type of the stirring device, the composition of the composition, etc.

[0169] For example, the composition can be prepared into a mixed product by mixing the particles and the binder while heating, and then mixing a solvent, an additive, etc. as needed. As for the mixed product, for example, it can be obtained in any shape such as filaments and particles that can be used for a 3D (three-dimensional) printer. The mixed product is three-dimensionally molded into a desired shape using a 3D printer, thereby obtaining a radio wave absorber (molded product). The shape of the radio wave absorber is not particularly limited, and can be any shape such as a flat shape and a linear shape. "Flat" includes sheet and film. Flat radio wave absorbers can also be called radio wave absorption plates, radio wave absorption sheets, radio wave absorption films, etc. The radio wave absorber can be a radio wave absorber of a single composition (for example, a single-layer radio wave absorption plate), or it can be a combination of two or more parts with different compositions (for example, a laminate). In addition, the radio wave absorber can have a planar shape, a three-dimensional shape, or a combination of a part with a planar shape and a part with a three-dimensional shape. As for the planar shape, for example, sheet and film shapes can be cited. Examples of the three-dimensional shape include a tube shape (circular tube shape, square tube shape, etc.), a trumpet shape, and a box shape (for example, at least one surface is open).

[0170] For example, from the viewpoint of ease of handling, the thickness of the radio wave absorber is preferably 20.0 mm or less, more preferably 10.0 mm or less, and further preferably 5.0 mm or less. From the viewpoint of mechanical properties, the thickness is preferably 1.0 mm or more, and more preferably 2.0 mm or more. In addition, when the radio wave absorber is a laminate, the thickness refers to the total thickness of the radio wave absorber constituting the laminate. The thickness of the radio wave absorber can be measured using a digital length measuring machine, for example, it can be the arithmetic average of the measured values ​​measured at 9 randomly selected locations.

[0171] <Three-dimensional modeling>

[0172] In the above-mentioned manufacturing method, the above-mentioned composition is three-dimensionally molded by a three-dimensional printer. "Three-dimensional (3D) printer" refers to a general term for a device that can directly mold a three-dimensional object from three-dimensional data by adding materials on a workbench (also called a "platform"). In the above-mentioned manufacturing method, for example, a 3D printer of a hot melt lamination (FDM: fused deposition modeling) method (also called a "hot melt lamination method") can be used. In a 3D printer of a hot melt lamination method, for example, three-dimensional molding can be performed as follows. Filaments of molding material can be supplied to the nozzle of the 3D printer, heated and melted in the nozzle to soften it and extruded from the nozzle, and stacked (i.e., stacked) on the workbench to obtain a three-dimensional object. If one direction within the plane of the workbench of the 3D printer is set as the X direction, the direction orthogonal to the X direction within the plane is set as the Y direction, and the vertical direction relative to the workbench is set as the Z direction, then, for example, the X direction becomes the thickness direction of the molded three-dimensional molded product. In this case, for example, the molding material can be stacked (stacked) along the Z direction on the workbench. Figure 1 This is an explanatory diagram of three-dimensional modeling using a 3D printer using a hot melt lamination method. The three-dimensional modeling using a 3D printer using a hot melt lamination method is formed on a workbench 2 Figure 1 In the case of the flat molded product 1 shown, the flat molded product can be molded into a three-dimensional object by depositing (stacking) the molding material in the Z direction while moving the nozzle in the X direction and the Y direction.

[0173] The 3D printer used in the above manufacturing method is not particularly limited, and a commercially available 3D printer or other 3D printer having a known structure can be used. The setting conditions of the 3D printer during three-dimensional modeling can be appropriately determined according to the shape of the molded product to be molded.

[0174] The radio wave absorber manufactured by the above manufacturing method can be incorporated into various articles that are preferably endowed with radio wave absorbency. The radio wave absorber formed directly into a desired three-dimensional shape from three-dimensional data can be incorporated into an article by three-dimensional modeling using a 3D printer. Furthermore, for example, a flat radio wave absorber can be incorporated into an article in any form, such as directly or by bending any part.

[0175] As a radar that has attracted attention in recent years, the vehicle-mounted radar is a radar that uses radio waves in the millimeter wave frequency band. Millimeter waves refer to electromagnetic waves with a frequency of 30.0 GHz to 300.0 GHz. For example, in order to reduce the side lobes of the vehicle-mounted millimeter wave radar, the above-mentioned radio wave absorber is preferably assembled on the front side (the incident side of the radio waves incident from the outside) of the radio wave transceiver unit in the vehicle-mounted radar.

[0176] Furthermore, the above-mentioned radio wave absorber can also be assembled in radio wave absorbing articles used in the field of wireless technology such as motion sensors. The above-mentioned radio wave absorber is preferably used as a radio wave absorber for improving recognition accuracy by removing unnecessary radio waves in wireless devices such as internal sensors of mobile phones and living information sensors. The radio wave absorber can be preferably used in 55.0-66.0GHz band radio wave absorbing articles, for example. Radio wave absorbing articles refer to articles that have radio wave absorbency with respect to radio waves of more than one frequency, and the above-mentioned radio wave absorbency can be brought about by assembling a radio wave absorber as at least a part of the article. 55.0-66.0GHz band radio wave absorbing articles refer to articles that have radio wave absorbency with respect to radio waves of more than one frequency in the frequency band of 55.0-66.0GHz. As such articles, for example, the various wireless devices mentioned above can be cited. By assembling the above-mentioned radio wave absorber in such radio wave absorbing articles, unnecessary radio waves can be removed and recognition accuracy can be improved.

[0177] In addition, depending on the type of radar used for the radio wave absorber, the bandwidth may become a wideband. For example, a 60 GHz band radar may be used in a bandwidth of 7.0 GHz within a range of 57.0 to 64.0 GHz. For radar applications with such a wide bandwidth, a plurality of particles selected from a group including magnetic particles and dielectric particles may be mixed to produce a radio wave absorber that can cope with the wideband and / or a plurality of radio wave absorbers may be mixed to produce a radio wave absorber that can cope with the wideband.

[0178] [Radio wave absorber]

[0179] One embodiment of the present invention relates to a radio wave absorber, comprising magnetic particles and a binder, wherein an arbitrary axial direction in a plane perpendicular to the thickness direction of the radio wave absorber is set as a 0° direction, and based on the axial direction, a direction rotated 30° in the clockwise direction, a direction rotated 60° in the clockwise direction, a direction rotated 90° in the clockwise direction, a direction rotated 120° in the clockwise direction, and a direction rotated 150° in the clockwise direction are set as a 30° direction, a 60° direction, a 90° direction, a 120° direction, and a 150° direction, respectively, and among the rectangular ratios measured in the thickness direction, the 0° direction, the 30° direction, the 60° direction, the 90° direction, the 120° direction, and the 150° direction of the radio wave absorber, the maximum value is set as SQ max , set the minimum value to SQ min , SQ max With SQ min The ratio (SQ max / SQ min) is less than 1.35. “SQ” is the abbreviation of Squareness Ratio, “max” is the abbreviation of maximum, and “min” is the abbreviation of minimum.

[0180] In the present invention and this specification, the rectangular ratio is measured for a measurement sample using the radio wave absorber itself as the measurement sample or a measurement sample cut out from the radio wave absorber as the measurement sample. The shape and size of the measurement sample are not particularly limited as long as they can be measured in a measurement device. When the measurement sample is cut out from the radio wave absorber as the measurement target, the measurement sample is cut while maintaining the thickness of the radio wave absorber as the measurement target. Therefore, the direction of the thickness of the measurement sample is the direction of the thickness of the radio wave absorber as the measurement target. For each measurement direction, the rectangular ratio is measured by the following method. The measurement direction of the rectangular ratio refers to the direction in which the magnetic field is applied during the measurement.

[0181] In a vibrating sample magnetometer, the magnetization intensity of the measurement sample relative to the applied magnetic field is measured under the conditions of a maximum applied magnetic field of 50 kOe and a magnetic field scanning speed of 104 Oe / sec at an ambient temperature of 23°C. A magnetic field (H)-magnetization (M) curve is obtained for the measurement sample based on the measurement results. From the obtained magnetic field (H)-magnetization (M) curve, the saturation magnetization (σs) and residual magnetization (σr) (unit: Am 2 / kg), and calculate the squareness ratio (SQ: Squareness Ratio) as "σr / σs". Regarding the unit, 1Am 2 / kg = 1emu / g, 1kOe = (10 6 / 4π)A / m.

[0182] Regarding the rectangular ratio of the test sample,

[0183] The direction of the thickness of the measurement sample, that is, the direction of the thickness of the radio wave absorber to be measured, and

[0184] An arbitrary axial direction within a plane perpendicular to the thickness direction is set as the 0° direction, and the directions rotated 30°, 60°, 90°, 120°, and 150° clockwise based on the axial direction are set as the 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction, respectively; and the 0° direction, 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction are set as the

[0185] The measurement was performed in a total of 7 directions. Figure 2 This is an explanatory diagram of an example of the measurement direction of the rectangular ratio. Figure 2Specific examples of the 0° direction, 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction are shown. Figure 2 The example shown is an example. An arbitrary axial direction within a plane perpendicular to the thickness direction is randomly selected as the 0° direction, and based on the determined 0° direction, the 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction are determined.

[0186] In the above-mentioned radio wave absorber, the maximum value Q of the squareness ratio measured in each of the above-mentioned seven directions is max With minimum SQ min The ratio (SQ max / SQ min ) is less than 1.35. Thus, a radio wave absorber having a small difference in the squareness ratio measured in various measurement directions has less polarization dependence and is therefore preferred. From the viewpoint of further reducing polarization dependence, the above ratio (SQ max / SQ min ) is preferably 1.34 or less, more preferably 1.32 or less, and further preferably 1.30 or less, 1.28 or less, 1.26 or less, 1.24 or less, 1.22 or less, 1.20 or less, 1.18 or less, 1.16 or less, 1.14 or less, 1.12 or less, and 1.10 or less. The above ratio (SQ max / SQ min ) can be, for example, 1.00 or more or more than 1.00. max / SQ min ) is 1.00, the rectangular ratios measured in the above-mentioned 7 directions are all the same value.

[0187] For example, according to the above-mentioned manufacturing method described in detail above, the above-mentioned ratio (SQ max / SQ min ) is less than 1.35. In one embodiment, the aspect ratio of the magnetic particles contained in the above-mentioned radio wave absorber can be less than 3.0. Regarding the aspect ratio of the magnetic particles contained in the above-mentioned radio wave absorber and other details, reference can be made to the previous records related to the above-mentioned manufacturing method. Among them, as long as the above-mentioned radio wave absorber contains magnetic particles and a binder and the above-mentioned ratio (SQ max / SQ min ) can be less than 1.35, and is not limited to the radio wave absorber manufactured by the above-mentioned manufacturing method.

[0188] For details of the radio wave absorber, reference can be made to previous descriptions related to the production method and the radio wave absorber produced by the production method.

[0189] [Radio wave absorbing items]

[0190] One embodiment of the present invention relates to a radio wave absorbing article including the above-mentioned radio wave absorber. As a specific example of the radio wave absorbing article, a vehicle-mounted radar can be cited. As a specific example, wireless devices such as internal sensors of mobile phones and living information sensors can also be cited. Moreover, in one embodiment, the above-mentioned radio wave absorbing article can be a 55.0GHz to 66.0GHz band radio wave absorbing article. The above-mentioned radio wave absorbing article can be any article including the radio wave absorber involved in one embodiment of the present invention, and there is no particular limitation on other structures, and known technologies related to radio wave absorbing articles can be applied.

[0191] Example

[0192] Hereinafter, the present invention will be described based on examples. However, the present invention is not limited to the embodiments shown in the examples. Unless otherwise specified, the processes and evaluations described below are carried out in an air atmosphere. Furthermore, unless otherwise specified, the processes and evaluations described below are carried out at an atmospheric temperature of 23°C ± 1°C. Hereinafter, "powder of magnetic particles" will be described as "magnetic powder", "powder of dielectric particles" will be described as "dielectric material", and they will be described as "radio wave absorbing materials".

[0193] [Preparation of magnetic powder A]

[0194] 15.72 g of strontium carbonate [SrCO3], 81.49 g of α-iron (III) oxide [α-Fe2O3] and 15.72 g of aluminum oxide [Al2O3] were weighed, and put into a paint shaker together with 500 g of zirconium oxide beads (bead diameter: 0.5 mm) and 300 g of water. The mixture was mixed in the paint shaker for 3.5 hours to obtain a dispersion.

[0195] After the mixing treatment, the dispersion liquid was recovered while separating the zirconia beads.

[0196] The recovered dispersion was centrifuged and the supernatant was discarded, and then dried in a heating furnace at a furnace temperature of 95° C. for 12 hours to obtain a raw material mixture.

[0197] Next, the obtained raw material mixture was subjected to a pulverization treatment for 30 seconds three times using a grinder (Absolute 3 manufactured by OSAKA CHEMICAL Co., Ltd.) with the variable speed dial set to “maximum”, thereby obtaining a powder.

[0198] The obtained powder was subjected to the following treatment as flux treatment.

[0199] Strontium chloride (SrCl2) is dissolved in 100 mL of water to prepare a 10% by mass concentration strontium chloride aqueous solution, which is added to the powder obtained above. After ultrasonic dispersion for 10 minutes, it is dried in a heating furnace at a furnace temperature of 95°C for 12 hours and then crushed by the above-mentioned grinder to obtain a crushed product.

[0200] Next, the obtained pulverized material was calcined in a heating furnace at a furnace temperature of 1250°C for 4 hours, and then the obtained calcined material was pulverized three times for 30 seconds using the above-mentioned grinder with the variable speed dial set to "5". It was then cleaned by ultrasonic treatment until the electrical conductivity reached less than 30 μS (microSiemens), and then dried in a heating furnace at a furnace temperature of 95°C for 12 hours to obtain magnetic powder.

[0201] Next, the obtained magnetic powder was subjected to an annealing treatment in a heating furnace at a furnace temperature of 1000° C. for 2 hours.

[0202] In this way, magnetic powder A was obtained.

[0203] [Preparation of magnetic powder B]

[0204] Magnetic powder B was obtained by the method described in connection with the preparation of magnetic powder A except that flux treatment was not performed.

[0205] [Confirmation of crystal structure]

[0206] The crystal structure of the magnetic substance constituting each of the magnetic powders described above was confirmed by X-ray diffraction analysis. As a measuring device, X'Pert Pro of PANalytical, which is a powder X-ray diffraction device, was used. The measuring conditions are shown below.

[0207] -Measurement conditions-

[0208] X-ray source: CuKα rays

[0209] 〔wavelength: (0.154nm, output: 40mA, 45kV)

[0210] Scanning range: 20°<2θ<70°

[0211] Scanning interval: 0.05°

[0212] Scanning speed: 0.33° / min

[0213] From the results of the X-ray diffraction analysis, it was confirmed that all the magnetic powders had a magnetoplumbite crystal structure and were single-phase magnetoplumbite hexagonal ferrite powders that did not include a crystal structure other than the magnetoplumbite crystal structure.

[0214] [Confirmation of composition]

[0215] The composition of the magnetic substance constituting each of the magnetic powders described above was confirmed by high-frequency inductively coupled plasma emission spectrometry. Specifically, the composition was confirmed by the following method.

[0216] A container (beaker) containing 12 mg of magnetic powder and 10 mL of a hydrochloric acid aqueous solution with a concentration of 4 mol / L was kept on a hot plate set at a temperature of 120°C for 3 hours to obtain a solution. After adding 30 mL of pure water to the obtained solution, it was filtered using a membrane filter with a filter pore size of 0.1 μm. The elemental analysis of the filtrate thus obtained was performed using a high-frequency inductively coupled plasma emission spectrometer [ICPS-8100 manufactured by Shimadzu Corporation]. Based on the results of the elemental analysis obtained, the content of each atom relative to 100 atomic % of iron atoms was calculated. Moreover, based on the obtained content, the composition of the magnetic body was confirmed. As a result, it was confirmed that the composition of magnetic powders A and B was a composition in which A in Formula 1 is Sr and x is 1.65.

[0217] [Measurement of aspect ratio]

[0218] Regarding the magnetic powder A and the magnetic powder B, a portion of the powder was collected and the aspect ratio was determined by the method described above.

[0219] A portion of powder was also collected from dielectric material A and dielectric material B described later, and the aspect ratio was determined by the method described above.

[0220] Table 1 shows the aspect ratios obtained for the magnetic powder and the dielectric material.

[0221] [Example 1, Comparative Example 1]

[0222] The magnetic powder shown in Table 1 was mixed in an amount such that the volume filling rate of the magnetic particles in the produced radio wave absorber reached 20 volume %, and a binder (polylactic acid: TERRAMAC TP-4030 manufactured by UNITIKA LTD.) and an antioxidant (Adekastab AO-60 manufactured by ADEKA CORPORATION) in an amount such that the volume filling rate of the binder in the produced radio wave absorber reached 79.5 volume %, thereby preparing a mixture.

[0223] The prepared mixture was formed into a filament using a Compounding Tester manufactured by TECHNOVEL CORPORATION, thereby producing a filament for a 3D printer having a diameter of 2.85 mm.

[0224] The 3D printer filament obtained above was installed in a 3D printer (S5 manufactured by Ultimaker) of hot melt lamination method, and the 3D printer was set to the conditions of nozzle temperature 200°C, table temperature 60°C, lamination pitch 0.1mm, and drawing speed 30mm / sec. Figure 1 As shown in FIG. 1 , the nozzle was moved in the X direction and the Y direction with the Z direction as the stacking direction to perform three-dimensional molding. In this way, a radio wave absorber (three-dimensional molding) was obtained as a 2.0 mm ( Figure 1 in the X direction) and the size is 110 mm ( Figure 1 Center, Y direction)×110mm( Figure 1 A flat molded product (in the Z direction).

[0225] [Comparative Example 2]

[0226] A radio wave absorber was obtained by the method described in Comparative Example 1 and Example 1 except that graphite CNP-35 manufactured by ItoGraphite Co., Ltd. was used as dielectric material A instead of magnetic powder in an amount so that the volume filling rate of dielectric particles in the produced radio wave absorber became 20 volume %.

[0227] [Example 2]

[0228] A radio wave absorber was obtained by the method described in Comparative Example 1 and Example 1 except that carbon black #50 manufactured by ASAHI CARBON CO., LTD. was used as dielectric material B instead of magnetic powder in an amount so that the volume filling rate of dielectric particles in the produced radio wave absorber became 20 volume %.

[0229] The thickness of each radio wave absorber of the example and the comparative example was calculated as the arithmetic average of the values ​​measured at nine randomly selected locations using a digital length measuring machine [Litematic (registered trademark) VL-50A manufactured by Mitutoyo Corporation]. The thickness of each radio wave absorber was 2.0 mm.

[0230] [Measurement of transmission attenuation]

[0231] The transmission attenuation (unit: %) of each of the above-mentioned radio wave absorbers was measured.

[0232] As the measuring device, a vector network analyzer (product name: N5225B) from Keysight Technologies and a horn antenna (product name: RH12S23) from KEYCOM Corporation were used. By the free space method, the incident angle was set to 0°, the scanning frequency was set to 60 GHz to 90 GHz, the scanning interval was set to 0.05 GHz, and one plane of each of the above-mentioned radio wave absorbers was directed toward the incident side, and the S parameter was measured (the measuring system was a vertical polarized wave). The S21 of the S parameter at a frequency of 76.5 GHz was used as the transmission attenuation. In order to evaluate the polarization dependence, the radio wave absorber of the measuring object was rotated 15° each time with the direction perpendicular to the above-mentioned plane as the rotation axis direction, and 7 points were measured from 0° to 90°. The maximum and minimum values ​​of the measured transmission attenuation are shown in Table 1. Table 1 also shows the difference between the maximum and minimum values ​​of the transmission attenuation (maximum value - minimum value).

[0233] From the results shown in Table 1, it can be confirmed that in Examples 1 and 2, the polarization dependence is less than that in Comparative Examples 1 and 2 (the difference between the maximum and minimum values ​​of the transmission attenuation (maximum value - minimum value) is zero or less than that in Comparative Examples 1 and 2).

[0234] [Table 1]

[0235]

[0236] [Measurement of rectangular ratio]

[0237] A flat measurement sample (thickness 2.0 mm) having a square plane with a side length of 6.0 mm was cut out from each radio wave absorber of Example 1 and Comparative Example 1, and the squareness ratio was determined by the following method using a vibrating sample type magnetometer.

[0238] As a vibrating sample magnetometer, a vibrating sample magnetometer manufactured by TAMAGAWA Ltd. (model: TM-TRVSM5050-SMSL) was used. Under the measurement conditions described above, the saturation magnetization (σs) and residual magnetization (σr) were determined for each of the seven measurement directions described above. Based on the saturation magnetization (σs) and residual magnetization (σr) determined for each measurement direction, the squareness ratio (SQ) was calculated as "σr / σs" for each measurement direction. The maximum value SQ of the squareness ratios determined for each of the seven directions was calculated. max With minimum SQ min The ratio (SQ max / SQ min ). The results are shown in Table 2.

[0239] [Table 2]

[0240] Comparative Example 1 Example 1 <![CDATA[SQ max ]]> 0.69 0.52 <![CDATA[SQ min ]]> 0.51 0.51 <![CDATA[SQ max / SQ min ]]> 1.35 1.02

[0241] Industrial Applicability

[0242] One aspect of the present invention is useful in the technical field of various autonomous driving controls such as autonomous driving control of automobiles and in the field of wireless technology such as motion sensors.

Claims

1. A method for producing a radio wave absorber, comprising the step of three-dimensionally shaping a composition comprising one or more particles selected from the group consisting of magnetic particles and dielectric particles and a binder by a three-dimensional printer, The aspect ratio of the particles is 3.0 or less.

2. The method for producing a radio wave absorber according to claim 1, wherein: The particles are magnetic particles, The magnetic particles are hexagonal ferrite particles.

3. The method for producing a radio wave absorber according to claim 2, wherein: The hexagonal ferrite is a substituted hexagonal ferrite.

4. The method for producing a radio wave absorber according to claim 3, wherein: The substituted hexagonal ferrite is a magnetoplumbite hexagonal ferrite having a composition represented by the following formula 1: Formula 1 One thousand (12-x) AI x ZERO 19 In Formula 1, A represents one or more atoms selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 0.50≤x≤8.

00.

5. The method for producing a radio wave absorber according to claim 4, wherein: In Formula 1, the atom represented by A includes Sr.

6. The method for producing a radio wave absorber according to claim 1, wherein: The particles are dielectric particles, The dielectric particles are carbon particles.

7. A radio wave absorber comprising magnetic particles and a binder, An arbitrary axial direction in a plane perpendicular to the thickness direction of the radio wave absorber is defined as a 0° direction. Taking the axial direction as a reference, the direction of 30°, 60°, 90°, 120°, and 150° rotated clockwise are respectively designated as the 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction. The maximum value of the squareness ratios measured in the thickness direction, 0° direction, 30° direction, 60° direction, 90° direction, 120° direction, and 150° direction of the radio wave absorber is defined as SQ max , set the minimum value to SQ min , SQ max With SQ min Ratio SQ max / SQ min Less than 1.

35.

8. The radio wave absorber according to claim 7, wherein: The aspect ratio of the magnetic particles is 3.0 or less.

9. The radio wave absorber according to claim 7, wherein: The magnetic particles are hexagonal ferrite particles.

10. The radio wave absorber according to claim 9, wherein: The hexagonal ferrite is a substituted hexagonal ferrite.

11. The radio wave absorber according to claim 10, wherein: The substituted hexagonal ferrite is a magnetoplumbite hexagonal ferrite having a composition represented by the following formula 1: Formula 1 One thousand (12-x) AⅠ x ZERO 19 In Formula 1, A represents one or more atoms selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 0.50≤x≤8.

00.

12. The radio wave absorber according to claim 11, wherein In Formula 1, the atom represented by A includes Sr. 13 . A radio wave absorbing article comprising the radio wave absorber according to claim 7 .

Citation Information

Patent Citations

  • Electromagnetic wave absorber and method of manufacturing the same

    JP2015133416A